Combustion Modeling in Jet Engine Combustors - Johansson, Erik (My University, 2010)
In combustion, chemically stored energy is converted into thermal energy in a combustor and this thesis deals with premixed turbulent combustion. This means that fuel is premixed with air prior to the combustor and that the flow entering the combustor is turbulent. The thermal energy released in the combustor can be converted into for example kinetic energy in a propelling jet or shaft work by a turbo machine. To perform CFD calculations of combustion reactions, kinetic information needs to be provided to the CFD code. Usually, a global reaction mechanism, consisting of a reduced number of chemical reactions, provides this information by means of kinetic parameters for the chemical reactions involved. The global reaction mechanisms that are currently implemented in the commercial CFD codes CFX and Fluent for the combustion of propane and kerosene have been compared to detailed chemical reaction schemes. The investigations have been done using a perfectly stirred reactor model and the results show that the currently used global reaction mechanisms may under-estimate the time needed for ignition, i.e. the reactions may be too fast. Several global reaction mechanisms have been identified as interesting candidates to represent these combustion reactions in CFD calculations. To investigate the potential for more extensive global reaction mechanisms, CFD calculations have been performed. Unsteady calculations with both the original kinetic parameters and modified kinetic parameters in the currently used global reaction mechanism for propane combustion have been done for the Validation Rig experiment, conducted at Volvo Aero. The SAS-SST turbulence model has been used and to represent the interaction between turbulence and chemistry, the combined Eddy Dissipation and finite rate chemistry model has been employed. In these calculations, more modeled turbulent kinetic energy is created in the simulation with slower kinetics and less modeled turbulent kinetic energy is created in the simulation with faster kinetics, when comparing to the simulation with original kinetic parameters. When adding the resolved part of the turbulent kinetic energy to the modeled part, more turbulent kinetic energy is created in both simulations with modified kinetics. The temperature and velocity profiles are better predicted by both simulations with modified kinetics than the simulation with original kinetics. The results show that more accurate solutions can be obtained by modifying the kinetic parameters, which suggests that by adding more elaborate global reaction mechanisms even better results can be expected.
Keywords: Tillämpad matematik; Kemiteknik; Teknisk fysik; Applied mathematics; Chemical Engineering; Engineering physics